2016
DOI: 10.1177/0003319716651753
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Educational Needs in the “Real World” and Teaching of Vascular Surgery in Medical Schools

Abstract: The prevalence of peripheral arterial disease (PAD) is 3% to 10% in the general population, increasing to 15% to 20% in those older than 70 years. 1 The Reduction of Atherothrombosis for Continued Health survey showed that almost 66% of patients with PAD had clinical evidence of other vascular disease. 2 Coronary artery disease is the most common cause of death among patients with PAD (40%-60%), cerebral artery disease accounts for 10% to 20% of deaths, 1,2 and 10% of deaths have been attributed to other vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The importance of early exposure to specialties is showcased by a number of papers published [7][8][9][10][11][12][13][14] throughout the last few years. They assess the limitations in the medical school curriculum, with some showing that only 56% of medical students were exposed to vascular surgery at university.…”
Section: Exposurementioning
confidence: 99%
“…The importance of early exposure to specialties is showcased by a number of papers published [7][8][9][10][11][12][13][14] throughout the last few years. They assess the limitations in the medical school curriculum, with some showing that only 56% of medical students were exposed to vascular surgery at university.…”
Section: Exposurementioning
confidence: 99%
“…Schwartz et al studied the knowledge of internal medicine interns regarding the prevalence, screening, and treatment of vascular disease. Their findings demonstrated that residents scored moderately on these questions and were therefore not well equipped to handle vascular pathology due to gaps in their prior medical education ( 13 ). The Ankle-brachial Index (ABI) is a known and reliable vascular biomarker for the detection of PAD and for primary and secondary prevention of cardiovascular events.…”
Section: Future Directions Of Medical School Vascular Educationmentioning
confidence: 99%
“…The Ankle-brachial Index (ABI) is a known and reliable vascular biomarker for the detection of PAD and for primary and secondary prevention of cardiovascular events. Despite its importance in the diagnosis of PAD, Wyatt et al documented a poor level of baseline knowledge of calculation and interpretation of ABI among internal medicine residents, irrespective of the year of residency ( 13 ). These findings highlight an inadequacy of knowledge within the sphere of vascular care and requires attention as this could be related to general understanding, exposure, and interest of medical students in the patient pool largely treated by vascular surgeons.…”
Section: Future Directions Of Medical School Vascular Educationmentioning
confidence: 99%